A Novel Ruthenium(II) Complex With Lapachol Induces G2/M Phase Arrest Through Aurora-B Kinase Down-Regulation and ROS-Mediated Apoptosis in Human Prostate Adenocarcinoma Cells - De Grandis, Rone A.; Oliveira, Katia M.; Guedes, Adriana P. M.; dos Santos, Patrick W. S.; Aissa, Alexandre F.; Batista, Alzir A.; Pavan, Fernando R. (Frontiers in Oncology, 2021)
Lapachol is a well-studied natural product that has been receiving great interest due to its anticancer properties that target oxidative stress. In the present work, two novel lapachol-containing ruthenium(II) complexes [Ru(Lap)(dppm)(bipy)]PF6 (1) and [Ru(Lap)(dppm)(phen)]PF6 (2) [Lap = lapachol, dppm = 1,1`-bis(diphosphino)methane, bipy = 2,2`-bipyridine, phen = 1,10-phenantroline] were synthesized, fully characterized, and investigated for their cellular and molecular responses on cancer cell lines. We found that both complexes exhibited a potent cytotoxic effect in a panel of cancer cell lines in monolayer cultures, as well as in a 3D model of multicellular spheroids formed from DU-145 human prostate adenocarcinoma cells. Furthermore, the complex (2) suppressed the colony formation, induced G2/M-phase arrest, and downregulated Aurora-B on DU-145 cells. The mechanism studies suggest that complex (2) stimulate the overproduction of reactive oxygen species (ROS) and triggers caspase-dependent apoptosis as a result of changes in expression of several genes related to cell proliferation and caspase-3 and -9 activation. Interestingly, we found that N-acetyl cysteine, a ROS scavenger, suppressed the generation of intracellular ROS induced by complex (2), and decreased its cytotoxicity, indicating that ROS-mediated DNA damage leads the DU-145 cells into apoptosis. Overall, we highlighted that coordination of lapachol to phosphinic ruthenium(II) compounds considerably improves the antiproliferative activities of resulting complexes granting attractive selectivity to human prostate adenocarcinoma cells. The DNA damage response to ROS seems to be involved in the induction of caspase-mediated cell death that plays an important role in the complexes' cytotoxicity. Upon further investigations, this novel class of lapachol-containing ruthenium(II) complexes might indicate promising chemotherapeutic agents for prostate cancer therapy.